Modeling the link between organizational antecedents and consequence of key account management performance in business-to-business context - Ahmmed, Kawsar Ahmmed; Mohd Noor, Nor Azila (Assumption University, Thailand, 2014)
Key account management, a supplier company initiated approach, targeted at the most important customers to solve their complex requirements with special treatment that eventually ensures both parties’ financial and non financial objectives, is regarded as a vital concern of many companies’ sales efforts in business-to-business context. Based on the extant literature s, we introduce a theoretical framework highlighting organizational antecedents and repeat order as the consequence of key account management performance.We theorize the conditions under which organizational factors, including top management emphasis and team effort influence the performance of key account management approach.In addition, moderating effect of length of relationship on the relationship between key account management performance and repeat order is also presented.Theoretical and managerial implications are provided along with several future research directions.